Moho depth derived from gravity and magnetic data in the Southern Atlas Flexure (Algeria). (September 2016) - Meliani, O.; Bourmatte, A.; Hamoudi, M.; Haddoum, H.; Quesnel, Y.
Abstract: Existing aeromagnetic and gravity data were used to study the structure of the Southern Atlas Flexure (SAF) in Algeria. Forward and inverse numerical modelings were applied, giving access to the depth of the Moho and the Curie depth in this area. Our results suggest a maximum crustal thickness of about 48 km, and a Curie depth of about 20 km. We then discuss the implications of those results on the regional structure of the SAF, also using cross-sections built using 2D-geological modeling. Highlights: Estimate the depth of Moho using the gravimetric data over the southern Atlas flexure. Estimate the magnetic crust's base over the southern Atlas flexure. Build a forward model to derive the depth of the causative structures, according to regional geology and inversion results.